The Influence of Women Leadership and Learning Facilities on the Performance of Islamic Religious Education Teachers at State Madrasah Ibtidaiyah in Bandar Lampung City - Akmansyah, Muhammad; Mawardi J, M.; Rohman, Miftahur; Hasanah, Uswatun (Universitas Islam Negeri Raden Intan Lampung, 2022)
Teachers' efficacy in carrying out their responsibilities and functions as educators is inextricably linked to the success of Madrasah education. On the other hand, educational facilities and the Madrasah principal's leadership style frequently impact teachers' performance. This quantitative study will look into how female leadership, learning facilities, and all of these characteristics influence the performance of Islamic religious education teachers at the State Madrasah Ibtidaiyah in Bandar Lampung City. The SPSS statistics 23 programs were used to perform multiple regression analysis in this quantitative study. The findings revealed that: (1) there is no significant effect of female Madrasah leadership on the performance of Islamic religious teachers; (2) learning facilities have a significant effect on the performance of Islamic religious teachers; (3) female Madrasah principals and Madrasah facilities together have a significant influence on the performance of Islamic religious teachers by 58.6%, and other factors influence the remaining 41.4%. As a result, the study's findings suggest that factors other than gender influence how well Islamic religious education teachers function at Bandar Lampung City's state Madrasah Ibtidaiyah. These criteria include aspects of the learning facility, separately and in conjunction with the leadership of the female Madrasah principal. As a result, more research is needed to look into various other factors that influence the efficiency of Madrasah teachers.